Synthesis, characterization, and molecular modeling studies of novel polyurethanes based on 2,2 '-[ethane-1,2-diylbis(nitrilomethylylidene)]diphenol and 2,2 '-[hexane-1,6-diylbis(nitrilomethylylidene)]diphenol hard segments - Raghu, A. V.; Gadaginamath, G. S.; Jawalkar, S. S.; Halligudi, Shivaraj B.; Aminabhavi, T. A. (Journal of Polymer Science Part A-Polymer Chemistry, 2006)
Novel polyurethanes (PUS) based on 2,2 `-[ethane-1,2-diylbis(nitrilomethylylidene)]diphenol and 2,2 `-[hexane-1,6-diylbis(nitrilomethylylidene)]diphenol as hard segments containing four aromatic diisocyanates (4,4 `-diphenylmethane diisocyanate, toluene 2,4-diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate) have been prepared. Fourier transform infrared, UV spectrophotometry, fluorescence spectroscopy, H-1 NMR and C-13 NMR spectroscopy, thermogravimetric analysis, and differential thermal analysis have been used to determine the structural characterization and thermal properties of the segmented PUS. All the PUS contain domains of both semicrystalline and amorphous structures, as indicated by X-ray diffraction. The acoustic properties have been calculated with the group contribution method. Molecular dynamics simulations have been performed on all the PUS to estimate the cohesive energy density and solubility parameter values, which compare well with the values calculated with the group contribution method. Furthermore, the simulation protocols have been applied to the PUS to produce X-ray diffraction plots to determine the phase morphology of the PUS. The surface properties of the PUS have been estimated from the simulation protocols. (c) 2006 Wiley Periodicals, Inc.
Keywords: amorphous; hard segments; molecular dynamics; Morphology; polyurethanes; Schiff base containing polymers; Thermal properties